Pliocene pedosedimentary cycles in the southern Pampas, Argentina - Kemp, R. A. (2000)
Well-developed Bt horizons of five palaeosols (P1-P5) have been recorded previously within a 20-m-thick succession of Pliocene siltstones and clayey siltstones in the southern part of the Buenos Aires Province of Argentina. This paper reports a detailed field and micromorphological (thin section) investigation of a 6-m portion of the sequence encompassing P2 and P3. Large-scale faunal burrow infillings occur throughout: other bioturbation features in the form of channel and spongy microstructures are mainly confined to the siltstones. The intervening clayey siltstones (Bt horizons) have been affected more by shrink-swell disruption, as evidenced by slickensides and a range of striated b-fabrics in thin sections. Clay coatings, indicative of illuvial accumulation of clay translocated in suspension from overlying A or E horizons, occur in both the siltstones and clayey siltstones. The types, microstratigraphic associations and depth functions of features are interpreted in terms of changing interactions, balances and dominances between sedimentary, pedogenic and erosional processes over time, thus providing the basis for the pedosedimentary reconstruction of landscape evolution in the region during part of the Pliocene represented by the whole P1-P5 sequence (4-5 Ma BP). It is envisaged that this period was dominated by aeolian deposition, although fluvial and mass movement processes probably led to reworking and redistribution of some of the materials. Overall rates of subaerial deposition, however, were not substantial: pedogenic processes were active throughout, the balance between sedimentation and pedogenesis varying over time in a cyclical fashion. Phases of reduced deposition and establishment of relatively stable land surfaces were marked by the development of argillic soil profiles with clearly defined eluvial and illuvial horizons. Intervening periods of more rapid accumulation of coarser material were characterized by accretionary soil development and welding of new pedological features on existing soils as the surface accreted, first transforming existing eluvial horizons into BCt/AE horizons (siltstones) and then encouraging the syndepositional upward extension of these complex horizons. The primary basis of the alternating units of siltstones (BCt/AE horizons) and clayey siltstones (Bt horizons) lies in the cyclical change in size of particles deposited, although pedogenic translocation processes enhanced these textural differences. The underlying driving mechanism behind the pedosedimentary cycle can only be speculated upon, although it is tempting to relate the sedimentation pattern to climatic fluctuations linked to glacial advances and retreats in the Patagonian Andes during the Pliocene.